SYNTHESIS OF 4-ALLYL-2-METHOXY-6-AMINOPHENOL FROM NATURAL EUGENOL - I Made Sudarma; Maria Ulfa; Sarkono Sarkono (Universitas Gadjah Mada, 2009)
The aim of this preliminary research was to synthesize derivatives of eugenol such as 4-allyl-2-methoxy-6-nitrophenol (2) and 4-allyl-2-methoxy-6-aminophenol (3). The result could be used as a reference on the transformation of eugenol to its derivatives. Theoriticaly nitration of eugenol (1) by nitric acid could produced 4-allyl-2-methoxy-6-nitrophenol (2) and followed by reduction could achieved 4-allyl-2-mehtoxy-6-aminophenol (3). The formation of this product was analyzed by analytical thin layer chromatography (TLC) and GC-MS. These analysis showed the formation of product (2) and (3) were visible. TLC showed product (1) less polar than eugenol and gave orange colour, and supported by GC-MS which showed molecular ion at m/z 209 due to the presence of -NO2 by replacing one H at 6 position of eugenol. Product (3) was afforded by reduction of (2) with Sn/HCl and tlc analysis showed compound (3) more polar than eugenol (1) and (2) and supported by GC-MS which showed molecular ion at m/z 179 due to the presence of -NH2.